The elderly in family health units: morbidity and use of health care services - Renata Cabrelli; Cristina Silva Sousa; Ruth Natalia Teresa Turrini; Tamara Iwanow Cianciarullo (Universidade Federal do Ceará, 2014)
This cross-sectional study aimed to identify the profile of morbidity and use of health services by the elderly in the Family Health Program Antonio Estevão de Carvalho, from São Paulo, Brazil. The information of 92 seniors from the database of the project "Family Health - assessment of the new assistance strategy in the setting of public policies" were used. A descriptive data analysis showed the elderly with an average age of 70.6 years old; 64.1%, females: 93.5% reported any kind of health problems, especially hypertension (67.4%) and diabetes mellitus (19.6%), 77.3% looked for health care; public hospitals (42.4%) were the most sought after services. The reasons for the choice of services were ease of access (18.5%) and need of care (7.6%). The main reason of satisfaction was the interpersonal care and of dissatisfaction the lack of medicines and the long wait to set appointments.